Pyogenic granuloma of tongue: A rare case report - Sharma, Sonam; Sharma, Amita; Kumar, Ashok; Kalhan, Shivani; Kaur, Jasmine (Asian Journal of Medical Sciences, 2014)
Pyogenic granuloma (PG) is a kind of inflammatory hyperplasia in response to chronic irritation. Here, we report a case of 64 year old male patient with PG on midline of the dorsum of the posterior third of the tongue. Its differential diagnosis, the importance of biopsy findings in establishing definitive diagnosis and about the new approaches for its treatment is discussed. DOI: http://dx.doi.org/10.3126/ajms.v6i3.10619 Asian Journal of Medical Sciences Vol.6(3) 2015 84-86